Istikhdâm Uslûb Ikhtibâr al-Kalimât fî Instagram li Mâdah al-Tarkîb litarqiyyati Tahṣîl al-Ṭulâb al-Dirâsi - Tamami, Fazri Nur Insan (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose - The purpose of this research is to determine the learning outcomes of students at Ma'had al-Jami'ah of the Persis Islamic Institute Bandung in the subject of 'tarkib' before and after the implementation of quiz techniques using Instagram as a medium. Design/Methodology/Approach- The method employed in this research is a Quasi Experiment with a pre-test and post-test design model. The data collected for this study is both qualitative, examining the conditions of the location, and quantitative, focusing on calculations. Data collection techniques involve a combination of observation, interviews, testing, research, and literature review. Findings - Referring to the research findings obtained in this study, it is evident that the learning outcomes of students at Ma'had al-Jami'ah of the Persis Islamic Institute Bandung in the subject of 'tarkib' before using the Instagram quiz technique yielded a score of 65 within the interpretation range of 60-65, indicating a good level. Following the implementation of the Instagram quiz method in the 'tarkib' subject, the post-test results yielded a score of 82 within the interpretation range of 80-89, denoting an excellent level. Furthermore, the N-Gen testing resulted in a score of 4.2%, implying that the use of the Instagram quiz technique in the subject matter has a significant impact on student scores at a moderate level. Research Limitation/Implications- The issue in this research is confined by directing the study's focus on the influence of using the Instagram quiz method within the subject of 'tarkib' among the students of Ma'had al-Jami'ah at STAI Persis Bandung.